Emotion recognition and theory of mind in schizophrenia: A meta-analysis of neuroimaging studies - Jáni, Martin; Kašpárek, Tomáš (The world journal of biological psychiatry, 2018)
OBJECTIVES: Patients with schizophrenia have difficulties processing the emotional and cognitive states of others. Neuroimaging studies show inconsistent findings. METHODS: We used a Seed-based d Mapping meta-analytic method to explore brain activation during facial emotion recognition and theory of mind tasks in schizophrenia patients. RESULTS: The patients showed lesser recruitment of the facial emotion processing network; behavioural performance was associated with the activation of the precentral gyrus. We found abnormal activation of the mentalising network in schizophrenia patients during reasoning about other people's mental states; patients with worse performances showed lesser activation in the right insula and superior temporal gyrus. Multimodal meta-analysis showed overlaps of brain-related abnormalities for both modalities in schizophrenia, with reduced recruitment of the right insula, anterior cingulate and medial prefrontal cortex and increased activation in the bilateral parietal cortex. Meta-regression results indicate that illness duration, medication and symptomatology might influence social-cognitive network disruptions in schizophrenia. CONCLUSIONS: These findings suggest the complex impairment of social cognition, as demonstrated by neural-related circuit disruptions during facial emotion processing and theory of mind tasks in schizophrenia.
Keywords: brain imaging; Magnetic Resonance Imaging; Behaviour; magnetická rezonanční tomografie; neurozobrazování; Social Behavior; Humans; Theory of Mind; mapování mozku; výraz obličeje; schizofrenie; Emotions; teorie mysli; sociální chování; lidé; Schizophrenia; schizofrenie (psychologie); schizophrenia; Schizophrenic Psychology; empathy; Brain Mapping; emoce; social cognition; Facial Expression; Neuroimaging